Synthesis and Structural Characterization of Furan-2,5-dicarbonylbis(N,N-diethylthiourea) and its Dinuclear Cu(II) and Zn(II) Complexes - Le Dinh Canh; Bui Quang Hoi; Nguyen Hong Nhung; Nguyen Huy Hung; Pham Chien Thang (My University, 2024)
Synthesis and Structural Characterization of Furan-2,5-dicarbonylbis(N,N-diethylthiourea) and its Dinuclear Cu(II) and Zn(II) Complexes
Keywords: Furan-2,5-dicarbonylbis